2014
DOI: 10.1016/j.addr.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Effective use of transdermal drug delivery in children

Abstract: Delgado

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 197 publications
(301 reference statements)
0
57
0
4
Order By: Relevance
“…Studies examining the thickness of various skin layers have shown that pig ear skin has a thickness similar to that of human skin (stratum corneum and epidermis). The follicular structure, vascular anatomy, and arrangement of collagen fibers in the dermis of the pig ear, as well as the content of glycosphingolipids and ceramides, are also similar to those of the human skin (Nair et al, 1997;Zorin, Kuylenstierna, Thulin, 1999;Heard et al, 2006;Klang et al, 2012;Chen, Han, Lian, 2013;Delgado-Charro, Guy, 2014).…”
Section: In Vitro Evaluation Of the Skin Permeation Of Drugsmentioning
confidence: 64%
See 2 more Smart Citations
“…Studies examining the thickness of various skin layers have shown that pig ear skin has a thickness similar to that of human skin (stratum corneum and epidermis). The follicular structure, vascular anatomy, and arrangement of collagen fibers in the dermis of the pig ear, as well as the content of glycosphingolipids and ceramides, are also similar to those of the human skin (Nair et al, 1997;Zorin, Kuylenstierna, Thulin, 1999;Heard et al, 2006;Klang et al, 2012;Chen, Han, Lian, 2013;Delgado-Charro, Guy, 2014).…”
Section: In Vitro Evaluation Of the Skin Permeation Of Drugsmentioning
confidence: 64%
“…Studies examining the thickness of various skin layers have shown that pig ear skin has a thickness similar to that of human skin (stratum corneum and epidermis). The follicular structure, vascular anatomy, and arrangement of collagen fibers in the dermis of the pig ear, as well as the content of glycosphingolipids and ceramides, are also similar to those of the human skin (Nair et al, 1997;Zorin, Kuylenstierna, Thulin, 1999;Heard et al, 2006;Klang et al, 2012;Chen, Han, Lian, 2013;Delgado-Charro, Guy, 2014).Skin permeation studies using inadequate protocols generate inaccurate data (Godin, Touitou, 2007). Thus, selection of the protocol must be performed by using experimental conditions, such as skin model, experimental apparatus, and receptor medium, appropriate for the formulation to be evaluated, and it must be based on the physicochemical properties of the drug, including aqueous solubility and oil-water partition coefficients.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…In another study, time to reach C max ranged from 18 to 66 h in children after patch application (25 lg/h) [104]. Transdermal pharmacokinetics is similar to those in adults [105][106][107].…”
Section: Transdermal Fentanylmentioning
confidence: 85%
“…Dermal and transdermal delivery systems have proven to be effective in reducing dose frequency, long duration of activity, achieving target delivery, easily administrating and avoiding hepatic first pass metabolism. [1][2][3][4] The stratum corneum, or horny layer, is the outermost layer of the skin and has been identified as the main barrier of the most drug permeation. Various strategies have been employed in attempts to improve the efficacy of topical delivery of drugs, including iontophoresis, electroporation, occlusion and ultrasound.…”
Section: Introductionmentioning
confidence: 99%